Water hyacinth-derived biopolyols for polyurethane production using crude glycerine as liquefaction solvent - Dy, Trixie Ruth N. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Water hyacinth -- an identified abandoned aquatic biomass -- was liquefied using locally sourced crude glycerine to produce biomass-derived polyols (biopolyols) suitable to replace petroleum-based polyols in polyurethane production. The liquefaction product containing the biopolyols was used to prepare rigid polyurethane ( PU) foams via one-pot mixing with a commercially sourced diisocyanate. The properties of the PU foams were determined by obtaining their densities, compressive strengths, thermal conductivities, and morphologies using the Scanning Electron Microscope (SEM). The biopolyols produced gave acid numbers and hydroxyl numbers within the recommended range for polyols fit for rigid polyurethane production. Fourier transform infrared spectroscopy (FTIR) results confirmed the presence of the OH group, which is the key functional group in the polyurethane reaction. The prepared rigid PU foams were found to have higher densities and compressive strengths, and relatively the same thermal conductivities compared to PU foams prepared from commercial mixes. SEM images show that rigid PU foam prepared using the biopolyol mix has more compact microstructures, hence their higher densities and compressive strengths. These results show the capability of the irigd PU foams in insulation application that require higher material strength. The secondary study was to use extracted biopolyols to synthesize PU microcapsules encapsulating n-Octadecane. The properties of the PU microcapsules were obtained using FTIR, Differential Scanning Calorimeter (DSC), and SEM. DSC results gave an average melting temperature of 28.98°C, which is within the human comfort range, and average heat of melting of 93.42 J/g. The microcapsules have potential in applications such as thermally-enhanced fabrics and insulation for cooling or buffering effect.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman
Keywords: Water hyacinth; Polyols; Polyurethanes; Liquefaction